Determination of non-organ specific autoantibodies in patients with chronic hepatitis C and association with HLA DRΒ1 (*04) allele - Ayub, Fatima; Tahir, Romeeza; Kashif, Muhammad; Javaid, Khursheed; Shahzad, Faheem; Jahan, Shah; Afzal, Nadeem (Universiti Kebangsaan Malaysia, 2022)
The regulation of immune mechanisms is controlled by major histocompatibility complex/human leukocyte antigen (MHC/HLA). Polymorphisms of the HLA region have an impact on susceptibility to complex infectious and autoimmune diseases. The present study was carried out to determine the frequencies of ASMA, AMA, ANA, dsDNA, and anti-LKM-1 auto-antibodies in hepatitis C patients and to determine their association with the HLA DRβ1 (*04) locus. It was a cross-sectional, analytical study, and 86 patients with chronic HCV were recruited. The presence of auto-antibodies (ASMA, AMA, ANA, dsDNA, and anti-LKM-1) was determined by indirect immunofluorescence and ELISA, while the HLA DRβ1 (*04) allele was assessed by sequence-specific conventional PCR. ANA was detected in 41%, ASMA in 17.4%, AMA in 7%, LKM-1 in 5.8% dsDNA in 4.6% of CHC patients while HLA-DRβ1 (*04) was present in 3.5% of patients, but this was not significantly associated with these auto-antibodies.